Efficacy of wastewater treatment on Arcobacter butzleri density and strain diversity. (15th November 2016) - Webb, Andrew L.; Taboada, Eduardo N.; Selinger, L. Brent; Boras, Valerie F.; Inglis, G. Douglas
Abstract: Arcobacter butzleri is a suspected waterborne enteric pathogen that is ubiquitous in the environment, but the degree to which wastewater treatment prevents entry of A. butzleri into environmental waters and the risks posed are not well established. Untreated and treated wastewater samples (n = 260) were collected weekly from the Lethbridge and Fort Macleod wastewater treatment facilities (the two major municipal inputs in southwestern Alberta, Canada) from May 2008 to April 2009. Untreated wastewaters contained high densities of A. butzleri and fecal coliform indicators, and densities at Lethbridge were typically higher than at Fort Macleod. Data indicated that A. butzleri and fecal coliform densities in wastewater were greatest in autumn and lowest in winter. Mechanical and biological treatment of wastewaters reduced but did not eliminate fecal coliform indicators or A. butzleri . At Lethbridge, UVB irradiation of mechanically and biologically treated wastewater further reduced densities of fecal coliform indicators. There was high A. butzleri genotype diversity in all sample sources, and survival during treatment was not strain-dependent. No genotype was dominant in any sample source, but 8.9% of genotypes were recurrent over time, and 4.4% of genotypes were detected at both wastewater treatment facilities. The current study demonstrates that viable A. butzleri are able to survive wastewater treatment, including UVB irradiation, which may lead to increased density and genetic diversity of this suspected pathogen in environmental waters via wastewater effluent discharge. Graphical abstract: Highlights: Wastewater treatment reduces but does not eliminate A. butzleri in effluent. Survival of A. butzleri in wastewater during treatment is not strain-dependent. A. butzleri entering environmental waters as wastewater effluent may pose a risk to human health.